Cluster synchronization in a complex dynamical network of non-identical nodes with delayed and non-delayed coupling via pinning control. (1st February 2019) - Liu, Lingfeng; Liu, Qian
Abstract: Synchronization of complex dynamical networks has been a hot topic for its practical applications. In this paper, the cluster synchronization of a complex dynamical network via pinning control is investigated. The nodes in different clusters are assumed to be non-identical. The network topology is assumed to be directed and non-symmetric. Both the non-delayed and delayed coupling are considered to be more realistic. Based on the Lyapunov stability theory, a simple and useful pinning control scheme is derived. Furthermore, numerical simulations show that our control strategy is quite effective and convenient.